Pengaruh Pertumbuhan Ekonomi Terhadap Pendapatan Asli Daerah Pada 38 Kabupaten/Kota Provinsi Jawa Timur Tahun 2020-2021 - Muhammad Syahroni; Oryza Ardhiarisca (Jurnal Akuntansi Terapan dan Bisnis, 2023)
This research aims to analyze and explain the effect of economic growth on local revenue in regencies/cities in East Java Province using quantitative methods. The data used in this study are secondary data in the form of time series obtained from the Central Bureau of Statistics of East Java Province and the Regional Financial Information System Data Portal (SIKD). In this study, data analysis techniques were used using simple regression analysis using the SPSS application. The results of this study indicate that economic growth in the Regencies/Cities of East Java Province significantly influences local own-source income. This is due to the large contribution of certain sectors to the Gross Regional Domestic Product (GRDP), especially in the sector of providing food and drink accommodation, as well as wholesale, retail, and car and motorcycle repair in 2020-2021.